Crosslinking mass spectrometry: A link between structural biology and systems biology. (6th March 2021) - Tang, Xiaoting; Wippel, Helisa H.; Chavez, Juan D.; Bruce, James E.
Abstract: Protein structure underpins functional roles in all biological processes; therefore, improved understanding of protein structures is of fundamental importance in nearly all biological and biomedical research areas. Traditional techniques such as X‐ray crystallography and more recently, cryo‐EM, can reveal structural features on isolated proteins/protein complexes at atomic resolution level and have become indispensable tools for structural biology. Crosslinking mass spectrometry (XL‐MS), on the other hand, is an emerging technique capable of capturing transient and dynamic information on protein interactions and assemblies in their native environment. The combination of XL‐MS with traditional techniques holds potential for bridging the gap between structural biology and systems biology approaches. Such a combination will enable visualization of protein structures and interactions within the crowded macromolecular environment in living systems that can dramatically increase understanding of biological functions. In this review, we first discuss general strategies of XL‐MS and then survey recent examples to show how qualitative and quantitative XL‐MS studies can be integrated with available protein structural data to better understand biological function at systems level.